2006
DOI: 10.1021/np0603368
|View full text |Cite
|
Sign up to set email alerts
|

Chloro- and Bromophenols from Cultures of Mycena alcalina

Abstract: Three new chlorinated phenols have been isolated from mycelial cultures of the mushroom Mycena alcalina. Their structures were determined by mass spectrometry and 1D and 2D NMR experiments. Addition of bromide to the medium resulted in the production of the corresponding brominated phenols. In addition, small amounts of the nonhalogenated precursor were also isolated, indicating that the halogenated metabolites are generated by a regioselectively operating halogenase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Compounds 4-6 were identified as the previously reported natural products, 3-methoxy-5-methylbenzene-1,2-diol (4) (Peters and Spiteller, 2006;Pouchert, 1993), daldinal B (5) (Hashimoto et al, 1994) and ergosta-4,6,8(14),22-tetraen-3-one (6) (Hashimoto et al, 1994;Fujimoto et al, 2004;Schulte et al, 1968) …”
Section: Identification Of Known Compoundsmentioning
confidence: 99%
“…Compounds 4-6 were identified as the previously reported natural products, 3-methoxy-5-methylbenzene-1,2-diol (4) (Peters and Spiteller, 2006;Pouchert, 1993), daldinal B (5) (Hashimoto et al, 1994) and ergosta-4,6,8(14),22-tetraen-3-one (6) (Hashimoto et al, 1994;Fujimoto et al, 2004;Schulte et al, 1968) …”
Section: Identification Of Known Compoundsmentioning
confidence: 99%
“…[48] In agreement with their bioactivity, investigations on the ecological role of the strobilurins demonstrated that S. tenacellus (German: Kiefernzapfenrübling), is able to prevent the growth of other fungi on the pine cone where the fungus grows. [5] Apart from the strobilurins, a number of other fungicides, such as pterulinic acid (19), [49] 4-O-acetyl hygrophorone A (20), [50] favolon (21) [51] or alcalinaphenol A (22), [52] have been isolated from mycelial cultures or fruiting bodies of higher fungi (Figure 3). Obviously, fungicides are wide- spread particularly in saprophytic fungi.…”
Section: Fungicidesmentioning
confidence: 99%
“…Accordingly, a GC-MS screening of trimethylsilylylated methanolic extracts from different Mycena species led to the identification of new chlorinated phenols, such as alcalinaphenol A (22), from mycelial cultures of Mycena alcalina. [52] Wound-Activated Chemical Defence…”
Section: Fungicidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, further biochemical studies are necessary to shed more light on this fascinating enzyme family, in particular as members of basidiomycete origin have remained completely uninvestigated, even though aromatic haloorganic natural products are known from these fungi. Besides the melleolides, examples include the alcalinaphenols from Mycena alcalina (54) and stephanosporin of Stephanospora caroticolor (55). Hence, our work represents the first biochemically and genetically characterized basidiomycete halogenases.…”
Section: Discussionmentioning
confidence: 98%